2018
DOI: 10.1016/j.tjog.2018.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Detection of fetal trisomy 9 mosaicism by noninvasive prenatal testing through maternal plasma DNA sequencing

Abstract: This case shows strong evidence that NIPT can be a powerful screening tool to detect rare fetal trisomies at very early gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Cases concerning Chr9 detected by NIPT are sporadic in the literature, and evidence regarding the efficacy of NIPT for the evaluation of Chr9 remains inconclusive. Three cases of fetal trisomy 9 mosaicism that were initially suspected after NIPT and verified by an invasive counterpart were reported by Lee et al (Lee et al, 2018 ). In a similar report, Ma et al predicted the approximate mosaic ratio of trisomy 9 using NIPT (Ma et al, 2015 ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Cases concerning Chr9 detected by NIPT are sporadic in the literature, and evidence regarding the efficacy of NIPT for the evaluation of Chr9 remains inconclusive. Three cases of fetal trisomy 9 mosaicism that were initially suspected after NIPT and verified by an invasive counterpart were reported by Lee et al (Lee et al, 2018 ). In a similar report, Ma et al predicted the approximate mosaic ratio of trisomy 9 using NIPT (Ma et al, 2015 ).…”
Section: Discussionmentioning
confidence: 92%
“…Numerous studies have confirmed the feasibility of NIPT for detecting common chromosomal aneuploidy (13/18/21), and a few publications have described the detection of rare chromosomal aneuploidy, mosaicism, and copy number variation using NIPT (Lee et al, 2018). Cases concerning Chr9 detected by NIPT are sporadic in the literature, and evidence regarding the efficacy of NIPT for the evaluation of Chr9 remains inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trisomy is responsible for the symptoms and physical anomalies that characterize T9MS. A recent case study supported the role of noninvasive prenatal testing by maternal plasma DNA sequencing as a potential mode of screening for T9MS [9].…”
Section: Hospital Coursementioning
confidence: 95%